PENGARUH IMPLEMENTASI NILAI-NILAI KARAKTER (TAAT, JUJUR, DISIPLIN, TANGGUNG JAWAB, DAN PERCAYA DIRI) TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS IV SD KRISTEN GENERASI UNGGUL KUPANG - Marseila Tabe, Reza; Bernard Mbuik, Heryon; Javier Hano, Alvin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is one of the primary focuses of elementary education in developing students with noble character, responsibility, discipline, honesty, obedience, and self-confidence. However, the implementation of character values in schools has not always produced optimal outcomes in students' behavior. This study aimed to determine the effect of implementing character values, including obedience, honesty, discipline, responsibility, and self-confidence, on the character formation of fourth-grade students at SD Kristen Generasi Unggul Kupang. This research employed a quantitative approach using a survey method. The population consisted of 28 fourth-grade students, all of whom were selected as the research sample. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, normality tests, linearity tests, simple linear regression, t-tests, and the coefficient of determination with the assistance of SPSS. The results indicated that the implementation of character values was categorized as high (78.6%), while students' character formation was categorized as very high (96.4%). The simple linear regression equation obtained was Y = 25.566 + 0.679X. The t-test showed a significance value of 0.000 (<0.05), indicating a significant positive effect of character value implementation on students' character formation. Furthermore, the coefficient of determination (R Square = 0.488) revealed that character value implementation contributed 48.8% to students' character formation. Therefore, the implementation of character values has a positive and significant influence on the character formation of fourth-grade students.